2012
DOI: 10.1186/1475-2875-11-135
|View full text |Cite
|
Sign up to set email alerts
|

The anaemia of Plasmodium vivax malaria

Abstract: Plasmodium vivax threatens nearly half the world’s population and is a significant impediment to achievement of the millennium development goals. It is an important, but incompletely understood, cause of anaemia. This review synthesizes current evidence on the epidemiology, pathogenesis, treatment and consequences of vivax-associated anaemia. Young children are at high risk of clinically significant and potentially severe vivax-associated anaemia, particularly in countries where transmission is intense and rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
185
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(198 citation statements)
references
References 193 publications
10
185
0
3
Order By: Relevance
“…However, the patterns on the rest of the country are not that similar at a visual inspection, and this is evidenced in a low correlation coefficient between these two variables (Spearman ρ=0.3). Some correlation between these two variables is to be expected, however, because malaria is frequently associated with anaemia (Douglas et al, 2012;Menendez et al, 2000). The other socioeconomic indicators showed patterns that differ from that of malaria incidence.…”
Section: Resultsmentioning
confidence: 94%
“…However, the patterns on the rest of the country are not that similar at a visual inspection, and this is evidenced in a low correlation coefficient between these two variables (Spearman ρ=0.3). Some correlation between these two variables is to be expected, however, because malaria is frequently associated with anaemia (Douglas et al, 2012;Menendez et al, 2000). The other socioeconomic indicators showed patterns that differ from that of malaria incidence.…”
Section: Resultsmentioning
confidence: 94%
“…Other factors, including immunological mechanisms with destruction of nRBCs or dysregulation and/or suppression of erythropoiesis, could be the mechanistic factors involved as previously proposed. 2,47 Iron deficiencies have also been identified as an important cause of anemia in populations living in malaria-endemic areas. 4,48 Interestingly, a high percentage of microcytic anemia (60%) has been reported in Colombian adults with malaria.…”
Section: Discussionmentioning
confidence: 99%
“…The present results showed that during blood stage propagation and development of PbANKA, % Hct level was markedly decreased and infected mice would die from severe hemolysis and anemia. The hemolysis induced by malaria infection is proposed to be a consequence of parasite development in RBC and exacerbated RBC membrane against products of oxidative stress releasing during infection [2,3]. Moreover, RBC destruction during blood stage of infection accumulates high levels of toxic free heme in circulation that, in turn, has the ability Anti-hemolytic activity of Siamese neem tree extract against Plasmodium berghei ANKA infected mice.…”
Section: Discussionmentioning
confidence: 99%
“…Over 90% of deaths occur within the continent of Africa, mainly among young children [2]. Malaria-associated hemolysis, one of the major life-threatening wellknown causes of death in P. falciparum and P. vivax malaria, occurs between 1-4% of hospitalized adult with a mortality that can reach up to 45% [3]. The pathogenesis of malaria-associated hemolysis is multifactorial and not well characterized, but several hypotheses suggest involvement of cytoadherence of infected red blood cells (iRBC), proinflammatory response as well as hemolysis due to oxidative stress [4].…”
Section: Introductionmentioning
confidence: 99%